An empirical study of voluntary research and development disclosures of biotechnology firms listed on NASDAQ - Gan, Peck Yen (2008)
This empirical study attempts to establish the relationship between a firm's voluntary disclosures on research and development and its size, growth options, leverage and its independent auditor's reputation. Based on the results of this study, it was established that for biotechnology firms listed on Nasdaq, there exists a positive relationship between voluntary disclosures on R&D and growth options and/or with firm size. It was also shown that leverage was an insignificant factor in influencing firms' voluntary disclosures on research and development. Due to a lack in variance in data collected, the relationship between voluntary disclosures on research and development and independent auditor's reputation could not be established.